Designing Customer Education Activities to Change People’s Perception of Catfish - Stevanus Pratama Suwito; Meidiahna Kusuma; Gamaliel Waney (Universitas Hayam Wuruk Perbanas, 2017)
Most people see catfish as an unhygienic fish, so less people want to consume it. In fact, catfish has better nutrition compared to Gourami. Therefore, catfish producers need to educate people. The purpose of this research is to design customer education activities to change people’s perception towards catfish using marketing communication mix. This research is a qualitative research and it uses in-depth interview method in gathering the required data. Based on the preliminary survey conducted to 50 people in Surabaya, it is known that Surabaya people are considered novice customers. As such, catfish producers can conduct customer education activities until people want to taste the catfish. The company can add picture, video, and oral information about the benefits in consuming catfish or the nutrition and the certificate of hygienic cultivation system. The producers can provide tester for the catfish and show the customers the comparison between good and bad quality catfish. The producers can also add two more marketing communication activities i.e. events and experiences as well as public relations and publicity. The producers need to use reliable sources in informing the catfish’s nutrition facts such as the certificate of catfish breeder, and certification from BPOM.